Production Facility Layout Redesign Using Systematic Layout Planning And Blocplan Methods - Mukhammad Hasan Bisri; Atikha Sidhi Cahyana (Procedia of Engineering and Life Science, 2022)
Layout of production facilities in CV. Jaya Rubber Industry was identified as less than optimal. The placement of production facilities that are less than optimal causes the distance between several departments to be far apart, for example in the cutting section to the molding section, the molding section to the trimming section and also the QC and packing sections to the finished goods warehouse. It was also found that intersecting material flows can cause backtracking, for example between molding to trimming and packing to the finished goods warehouse. These problems can result in the production process being less effective and efficient. This research combines two methods, namely systematic layout planning and blocplan methods. The systematic layout planning and Blocplan methods have several stages in planning the layout. This method is believed to be able to solve various problems that exist within the company such as production flow, transportation, warehousing, assembly and others. This method was chosen because the current industrial conditions require adjustments in the preparation of a good layout. The results of this study obtained a layout from the blocplan method which was chosen as the proposed layout with a total displacement distance of 44.25 with a decrease in distance of 23.75 m from the initial distance, with an efficiency level of 34% which was able to improve the flow of the production process for the better.